2016
DOI: 10.1080/15384101.2016.1147633
|View full text |Cite
|
Sign up to set email alerts
|

MiRImpact, a new bioinformatic method using complete microRNA expression profiles to assess their overall influence on the activity of intracellular molecular pathways

Abstract: MicroRNAs (miRs) are short noncoding RNA molecules that regulate expression of target mRNAs. Many published sources provide information about miRs and their targets. However, bioinformatic tools elucidating higher level impact of the established total miR profiles, are still largely missing. Recently, we developed a method termed OncoFinder enabling quantification of the activities of intracellular molecular pathways basing on gene expression data. Here we propose a new technique, MiRImpact, which enables to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 35 publications
(41 reference statements)
1
13
0
Order By: Relevance
“…These profiles were markedly different for the fibroblasts with high and low sensitivity to infection at both levels of RNA regulation. Similarly to the previously published data for bladder cancer, 23 we observed that the intracellular pathway regulation at the miR level differs greatly from that at the mRNA level, thus showing orthogonal dependencies for the extent of pathway activation (Fig. 4).…”
Section: Hcmv Infection-linked Changes In Gene and Molecular Pathway supporting
confidence: 89%
See 2 more Smart Citations
“…These profiles were markedly different for the fibroblasts with high and low sensitivity to infection at both levels of RNA regulation. Similarly to the previously published data for bladder cancer, 23 we observed that the intracellular pathway regulation at the miR level differs greatly from that at the mRNA level, thus showing orthogonal dependencies for the extent of pathway activation (Fig. 4).…”
Section: Hcmv Infection-linked Changes In Gene and Molecular Pathway supporting
confidence: 89%
“…To assess pathway regulation at the microRNA (miR) level, we used the MiRImpact method recently developed in our consortium. 23 The algorithm MiRImpact was built to characterize the effects, provoked by the changes in overall miR concentrations. It quantifies their impact on the activity of intracellular molecular pathways.…”
Section: Profiling Of Rna Expression and Activation Of Molecular Pathmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent modifications to the OncoFinder algorithm allow the personalized screening of nootropic drugs, 60 as well as the analysis of the effects of small RNA (MiRImpact) on signaling pathways. 61 With thorough animal studies, OncoFinder and MiRImpact may be further developed and enabled to predict possible targeted chemotherapy-induced brain side effects.…”
Section: Reflections and Future Perspectivesfrom Mechanisms To Aging mentioning
confidence: 99%
“…Notably, the changes in expression of microRNA may also affect expression levels of other, non-target mRNAs, for example, due miRNA targeting of their upstream regulators. Consequently, newer, more comprehensive approaches, like miRImpact (Artcibasova et al, 2016), PanMiRa (Li and Zhang, 2014), and ProMISe (Li et al, 2014), aim at explaining complex phenotypes by performing analysis of each microRNAs along with its direct and indirect targets.…”
Section: Introductionmentioning
confidence: 99%